(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
In Ayurveda it is necessary to reveal basic concepts, without which one cannot achieve good practice because many treatment approaches are hidden in basic concepts. In this aspect, Rasa, Guna, Veerya, Vipaka, Prabhava and Karma constitute basic concepts of Dravyaguna. Stambhana and Grahi comes under heading of karma, both do the same function of checking the excess flow but applicable in different conditions, having different mechanism of action. Grahi karma is different from Stambhana karma in performing Deepana and Pachana. Stambhana karma is applicable in excess flow of all the Srotas and Grahi karma is restricted to Purishavaha, Udakavaha, Annavaha srotas. Many drugs and formulations are explained in classics which perform Stambhana and Grahi action by their Rasadi Panchaka and Panchabhautik composition. Most of the Stambhana and Grahi drugs contain tannins, which help in ceasing excess flow of body fluids. Present article reveals the Stambhana, Grahi and Sangrahi karma along with its clinical applicability.